Réponses

Meilleure réponse !
  • Omnes
  • Modérateur confirmé
2014-04-07T22:36:35+02:00
Salut,

On sait qu'un polynôme de degrè 2 s'exprime sous la forme : ax² + bx + c. a, b et c étant appelés coefficients des fonctions

a.

f1(x) = (x+5)(x-2)
f1(x) = x² - 2x + 5x - 10
f1(x) = 1 + 3x - 10

Ici, a = 1, b = 3, c = -10

b.

f2(x) = (2x-1)²
f2(x) = 4- 4x + 1

Ici a = 4, b = -4, c = 1

c.

f3(x) = -2(x-3)² - 5
f3(x) = -2(x² - 6x + 9) - 5
f3(x) = -2x² + 12x - 18 - 5
f3(x) = -2+ 12x - 23

Ici; a = -2, b = 12, c = -23.


Bonne soirée !